2007
DOI: 10.1038/ni1500
|View full text |Cite
|
Sign up to set email alerts
|

The development of inflammatory TH-17 cells requires interferon-regulatory factor 4

Abstract: Interferon-regulatory factor 4 (IRF4) is essential for the development of T helper type 2 cells. Here we show that IRF4 is also critical for the generation of interleukin 17-producing T helper cells (T(H)-17 cells), which are associated with experimental autoimmune encephalomyelitis. IRF4-deficient (Irf4(-/-)) mice did not develop experimental autoimmune encephalomyelitis, and T helper cells from such mice failed to differentiate into T(H)-17 cells. Transfer of wild-type T helper cells into Irf4(-/-) mice rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
577
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 617 publications
(609 citation statements)
references
References 37 publications
24
577
2
6
Order By: Relevance
“…Furthermore, studies in patients with rheumatoid arthritis have suggested that overproduction of IL-17 is dependent on signal transduction pathways involving PI3K/Akt and NF-kB [70]. It has also been reported that IRF-4 is required for Th17 differentiation and IRF4-deficient are resistant to the development of EAE [71].…”
Section: Intracellular Signalling Molecules and Transcription Factorsmentioning
confidence: 99%
“…Furthermore, studies in patients with rheumatoid arthritis have suggested that overproduction of IL-17 is dependent on signal transduction pathways involving PI3K/Akt and NF-kB [70]. It has also been reported that IRF-4 is required for Th17 differentiation and IRF4-deficient are resistant to the development of EAE [71].…”
Section: Intracellular Signalling Molecules and Transcription Factorsmentioning
confidence: 99%
“…EAE was induced in 8-to 12-wk-old C57BL/6 mice by subcutaneous injection of 200 mg myelin oligodendrocyte glycoprotein peptide [48] (mevgwyrspfsrvvhlyrngk; synthesized by Dr. R. Volkmer, Charité, Berlin, Germany) emulsified in complete Freund's adjuvant (containing 1 mg/mL Mycobacterium tuberculosis H37RA, Sigma) together with i.v. administration of 200 ng pertussis toxin (Sigma) on days 0 and 2.…”
Section: Eae Inductionmentioning
confidence: 99%
“…*P-value o0.05 haplotypic differences compared to the controls. [27][28][29] Recent findings suggest that IRF4 is also involved in the development of Th17 cells 30 that are believed to be centrally involved in psoriasis. The polymorphisms rs1167846 in the IL20RA gene and rs747842 in the IL20RB gene appear as interesting candidates for further studies, however, these hypotheses are currently speculative and require functional support.…”
Section: Discussionmentioning
confidence: 99%